Theoretical Study of the C6H5NH2 + CH3 Reaction by the Density Functional Theory DFT/M06-2X/6-311++G(3df,2p) - Tran, Duc Chien; Nguyen, Duc Trung; Pham, Tien V. (JST: Engineering And Technology For Sustainable Development, 2022)
The mechanism of the reaction between Aniline compound (C6H5NH2) and Methyl radical (CH3•) has been studied by using the density functional theory DFT/M06-2X in conjunction with the 6-311++G(3df,2p) basis set for both optimization and single-point energy calculations. The calculated results indicate that the mechanism of the CH3• + C6H5NH2 reaction can occur in two different directions, namely, H-atom abstraction and addition. As a result, 13 various products have been created from this reaction; in which, P1 (C6H5NH + CH4) is the most thermodynamically stable product and the reaction path leading to this product is also the most energetically and kinetically favorable channel. The calculated thermodynamic properties for all reaction channels in the C6H5NH2 + CH3 system are in good agreement with the literature values derived from the Active Thermochemical Tables. The T1 diagnostics and the spin contamination effect of all species involved have insignificant multireference character and can be ignored.